SciVee 2011
DOI: 10.4016/37425.01
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for Inflammation Changes Estimates of Iron Deficiency among Rural Kenyan Preschool Children

Abstract: The assessment of iron status where infections are common is complicated by the effects of inflammation on iron indicators and in this study we compared approaches that adjust for this influence. Blood was collected in 680 children (aged 6-35 mo) and indicators of iron status [(hemoglobin (Hb), zinc protoporphyrin (ZP), ferritin, transferrin receptor (TfR), and TfR/ferritin index)] and subclinical inflammation [(the acute phase proteins (APP) C-reactive protein (CRP), and α-1-acid glycoprotein (AGP)] were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 9 publications
4
29
0
Order By: Relevance
“…Hemoglobin was suppressed in British, Zambian, and Zanzibari children during the APR and found to be inversely related to serum ferritin concentration, supporting its role as a reactive iron (23,131,168). In Kenyan children, hemoglobin was negatively correlated to CRP and AGP and positively associated with serum ferritin (169). Upon adjusting for inflammation, the relation between hemoglobin and the APPs disappeared and that with serum ferritin was strengthened (169).…”
Section: Apps As Markers Of Infection For Nutrition Interventionsmentioning
confidence: 74%
“…Hemoglobin was suppressed in British, Zambian, and Zanzibari children during the APR and found to be inversely related to serum ferritin concentration, supporting its role as a reactive iron (23,131,168). In Kenyan children, hemoglobin was negatively correlated to CRP and AGP and positively associated with serum ferritin (169). Upon adjusting for inflammation, the relation between hemoglobin and the APPs disappeared and that with serum ferritin was strengthened (169).…”
Section: Apps As Markers Of Infection For Nutrition Interventionsmentioning
confidence: 74%
“…14 The following thresholds were used to define abnormal values for these biochemical indicators: ferritin 12 μg/L in PSC and ferritin 15 μg/L in SAC 15 ; RBP 0.7 μmol/L; CRP 5 mg/L; AGP 1 g/L. 16 Because biomarkers of nutrition are influenced by inflammation, iron deficiency, vitamin A deficiency, and anemia were defined using a correction factor approach to adjust ferritin, RBP, and Hb values for the presence of inflammation, which was described previously. 16,17 Because the prevalence of inflammation varied by age, separate correction factors were calculated for PSC and SAC.…”
Section: Methodsmentioning
confidence: 99%
“…16 Because biomarkers of nutrition are influenced by inflammation, iron deficiency, vitamin A deficiency, and anemia were defined using a correction factor approach to adjust ferritin, RBP, and Hb values for the presence of inflammation, which was described previously. 16,17 Because the prevalence of inflammation varied by age, separate correction factors were calculated for PSC and SAC. Among PSC, correction factors for ferritin, RBP, and Hb were as follows: 0.87, 1.0, and 0.91 for early inflammation (elevated CRP and normal AGP); 0.36, 1.51, and 1.08 for early convalescent inflammation (elevated CRP and AGP); 0.78, 1.1, and 1.0 for late convalescent inflammation (elevated AGP and normal CRP).…”
Section: Methodsmentioning
confidence: 99%
“…Over a third and about half of the children had elevated acute and chronic acute-phase markers respectively. Similar proportions were obtained by Grant et al (2012) in their study in Western Kenya [9]. When the data was grouped by inflammation status, the proportion of children in the incubation group was low and this is comparable to other similar studies [9,10,24] although in a study in Indonesian infants, lower proportions were found in the early convalescence group [25].…”
Section: Discussionsupporting
confidence: 87%